Antitussive plants used in Mexican traditional medicine - Waizel-Bucay, José; Waizel-Haiat, Salomón (Pharmacognosy Reviews)
The plants have been used as antitussives agents due to their anti-inflammatory, antibiotic, antiviral, demulcents, expectorant and mucolytic properties, related with their ability to elaborate active principles such as aldehydes, alcohols, alkaloids, essential oils, glycosides, flavonoids, gums, ketones, lactones, mucilages, oleoresins, pectin, phenols, tannins and terpenoids. To know which plants are used in Mexican traditional medicine as antitussives, several texts and journals were consulted and analyzed. Results: This paper provides a comprehensive list of about 81 plants, belonging to 42 different families. They grow wild or cultivated in different Mexican regions; we present their scientific name and synonyms, the botanic family, their corresponding common name, part of the plant employed, form of preparation of the remedy, and some of their major active constituents or active principles. Asteraceae (Compositae), Lamiaceae (Labiatae), Boraginaceae, Rosaceae and Brassicaceae (Cruciferae), was the principal families reported, perhaps their secondary metabolites as i.e. sesquiterpenes and essential oils. The flowers, leaves, and aerial parts are most frequently used. The mainly common form of preparation is as decoction or infusion (tea) and the administration type is usually oral.
Keywords: Antitussive plants; cough medicine; medicinal plants; Mexican traditional medicine